2017
DOI: 10.1111/dme.13392
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the combination insulin bolus split for a high‐fat, high‐protein meal in children and adolescents using insulin pump therapy

Abstract: High-fat and high-protein meals require a ≥60% insulin:carbohydrate ratio as a standard bolus to control the initial postprandial rise. Additional insulin at an insulin:carbohydrate ratio of up to 70% is needed in the extended bolus for a high fat and protein meal to prevent delayed hyperglycaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(73 citation statements)
references
References 12 publications
2
71
0
Order By: Relevance
“…Bell et al showed that 65% more insulin was required with HFHP meals and that a 30%/70% split over 2.4 hours was the optimal insulin delivery pattern . Lopez et al tested different bolus strategies for HFHP meals in children and young adults with T1D and came to the same conclusion; the combination bolus 30%/70% split best maintained glucose control in the late postprandial period . However, they suggested that the total insulin bolus should be increased to allow administration of 60% of the calculated bolus initially and an additional 70% in the extended bolus .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bell et al showed that 65% more insulin was required with HFHP meals and that a 30%/70% split over 2.4 hours was the optimal insulin delivery pattern . Lopez et al tested different bolus strategies for HFHP meals in children and young adults with T1D and came to the same conclusion; the combination bolus 30%/70% split best maintained glucose control in the late postprandial period . However, they suggested that the total insulin bolus should be increased to allow administration of 60% of the calculated bolus initially and an additional 70% in the extended bolus .…”
Section: Discussionmentioning
confidence: 99%
“…10 Lopez et al tested different bolus strategies for HFHP meals in children and young adults with T1D and came to the same conclusion; the combination bolus 30%/70% split best maintained glucose control in the late postprandial period. 11 However, they suggested that the total insulin bolus should be increased to allow administration of 60% of the calculated bolus initially and an additional 70% in the extended bolus. 11 Additional long-term studies are needed to examine the efficacy and the applicability of these strategies.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…In the present study insulin was delivered as a combination bolus for each algorithm. Combination insulin boluses have been shown to be beneficial for high fat and protein meals (3,4,(16)(17)(18)(19). However, the optimal split and duration of the combination bolus have not yet been determined.…”
Section: Discussionmentioning
confidence: 99%
“…A good understanding of meal content and the glycaemic index is probably important for pump users to fully benefit from the effect of faster aspart. Although the use of faster aspart in the context of high‐ or low‐glycaemic index meals has not been addressed in clinical trials, there may be a need for different bolus types, such as a delayed/extended bolus with larger meals or a dual‐ or multi‐wave bolus for high‐fat and high‐protein meals (Figure ) . As a starting point for high‐fat and high‐protein meals, 30% of the total insulin dose can be administered immediately and 70% administered with a delay over the 2–4 hours following the meal.…”
Section: Faster Aspart Via Csii: Practical Considerationsmentioning
confidence: 99%
“…As a starting point for high‐fat and high‐protein meals, 30% of the total insulin dose can be administered immediately and 70% administered with a delay over the 2–4 hours following the meal. It should also be noted that more insulin than that calculated by carbohydrate counting alone may be needed …”
Section: Faster Aspart Via Csii: Practical Considerationsmentioning
confidence: 99%